ANÁLISE DE PRÁTICAS DISCURSIVAS: UMA ABORDAGEM METODOLÓGICA QUANTIQUALITATIVA - Sampaio, Maria Cristina Hennes (Intercâmbio, 2010)
The aim of this paper is to demonstrate how a quantiqualitative methodological approach, applied to a discoursive corpus, may orientate the construction and the analysis of a discoursive/dialogical network relations and answer to relevant questions of a research problem.